Gold/SH-functionalized nanographene oxide/polyamidamine/poly(ethylene glycol) nanocomposites for enhanced non-enzymatic hydrogen peroxide detection. (30th September 2020) - Hao, Bingjie; Song, Tao; Ye, Mao; Liu, Xuanyong; Qiu, Jiajun; Huang, Xiaoyu; Lu, Guolin; Qian, Wenhao
Abstract : AuNPs/SH-functionalized NGO/PEG/PAMAM nanocomposites show obvious responses to H2 O2 . Abstract : Hydrogen peroxide (H2 O2 ) is an important mediator in biological medicine, disease diagnosis and environmental analyses and therefore it is essential to develop a detection approach for H2 O2 in physical environments. Herein, we designed and prepared a series of AuNP-containing nanocomposites (AuNPs@NGO-PEG, AuNPs@G1-PAMAM-NGO-PEG and AuNPs@G3-PAMAM-NGO-PEG) for enhanced non-enzymatic H2 O2 detection. We firstly demonstrated functionalized nanographene oxide (NGO) based materials, which combined advantages of biocompatible poly(ethylene glycol) (PEG), hyperbranched polyamidamine (PAMAM) dendrimer and thiol active site, as compatible platforms. Gold nanoparticles (AuNPs) were then aptly in situ grown on these functionalized NGO based materials via the reduction of HAuCl4 under mild conditions, i.e. AuNPs@NGO-PEG, AuNPs@G1-PAMAM-NGO-PEG and AuNPs@G3-PAMAM-NGO-PEG nanocomposites, which possess stable and uniform AuNPs standing on the functionalized NGO sheets. For H2 O2 detection, these nanocomposites were cast on a glassy carbon electrode (GCE) conveniently, i.e. GCE/AuNPs@NGO-PEG, GCE/AuNPs@G1-PAMAM-NGO-PEG and GCE/AuNPs@G3-PAMAM-NGO-PEG. It is evident that these GCEs could be applied as efficient non-enzymatic H2 O2 detectors resulting from the corresponding cyclic voltammetric curves and typical ready-state amperometric curves. GCE/AuNPs@G1-PAMAM-NGO-PEG exhibited the fastest electron transfer rate among these modified GCEs. We envisage that these GCEs could provide efficient sensors for H2 O2 detection and a new strategy for sensor design.